2018
DOI: 10.3389/fneur.2018.00596
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Use of Acupuncture in Treating Parkinson's Disease: Update of Information From the Past 5 Years, a Mini Review of the Literature

Abstract: Acupuncture is an alternative therapy for Parkinson's disease (PD), but its efficacy and safety are controversial. Our previous study, which reviewed the literature from 1974 to 2012, could not find enough evidence from rigorously designed randomized, controlled trials (RCTs) to make a conclusion about the efficacy of acupuncture. Recently, more RCTs and meta-analyses have been conducted to evaluate the efficacy of acupuncture. The aim of our current study is to provide updated information in brief on this top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…Although the results of the meta-analysis indicated that acupuncture was effective in treating ICH, the quality of the included studies was quite weak according to the strict evaluation standards of EBM, which limited the worthiness of the evidence. Only limited evidence was obtained from this study, which is in agreement with most of the previous studies involved in TCM evaluation [1][2][3][4]. Our results indicated that lack of blinding and allocation concealment and high heterogeneity were the most dominant flaws in most of the TCM trials, which is attributed to the fundamental difference between TCM and Western medicine.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although the results of the meta-analysis indicated that acupuncture was effective in treating ICH, the quality of the included studies was quite weak according to the strict evaluation standards of EBM, which limited the worthiness of the evidence. Only limited evidence was obtained from this study, which is in agreement with most of the previous studies involved in TCM evaluation [1][2][3][4]. Our results indicated that lack of blinding and allocation concealment and high heterogeneity were the most dominant flaws in most of the TCM trials, which is attributed to the fundamental difference between TCM and Western medicine.…”
Section: Discussionsupporting
confidence: 86%
“…In our previous studies on the use of acupuncture to treat neurological diseases, [1,2] we searched thousands of literature reports regarding the efficacy of acupuncture, but we could not find even one paper that provided convincing evidence. Our recent follow-up study found some RCTs that provided limited evidence for the efficacy of acupuncture in the treatment of Parkinson's disease, but the evidence was still weak [3]. A recent systematic review by the Cochrane Library regarding Chinese herbs for lithiasis also came to the same conclusion [4].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…As an alternative and complementary therapy, acupuncture or electro-acupuncture (EA) has long been used to alleviate the symptoms of patients with PD and improve their quality of life [19][20][21]. Our studies have consistently demonstrated that high-frequency EA stimulation (100 Hz) alleviated movement disorders in multiple parkinsonian models [22][23][24][25].…”
Section: Introductionmentioning
confidence: 94%
“…It has been described as showing improvement in the UPDRS total score and in its subsections after an acupuncture session. So, even motor and nonmotor signs and symptoms, including pain, can be improved with the use of acupuncture [65][66][67]. However, the most important source of data that proves the beneficial effects of acupuncture in treatment of signs and symptoms in Parkinson's disease is provided from functional neuroimaging studies.…”
Section: Multimodal Exercise Programmentioning
confidence: 99%